2022
DOI: 10.3390/jmse10121889
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Organization Service for Maritime Autonomous Surface Ships (MASS) with Different Degrees of Autonomy

Abstract: Maritime Autonomous Surface Ships (MASS) have been an important direction for the development of intelligent shipping. However, most current international research on MASS focuses on navigation assistance technologies such as perception and decision-making, ignoring MASS’s traffic organization and management. The traffic organization service (TOS) under the e-Navigation strategy also has not researched MASS. In this paper, we propose the notion of on-demand service to MASS with different degrees of autonomy (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A previous study, ref. [45], showed that under Beaufort 7 wind conditions, when considering factors like ship length, water depth, and anchoring chain length, the radius is smaller than the radius derived from calculations involving the rule-based methods determined by Equation (8). Therefore, using the rule-based radius, as evident from the more conservative results presented in this paper, is considered a reasonable approach.…”
Section: Modeling Characteristic Regions Of the Port Of Ulsanmentioning
confidence: 71%
See 1 more Smart Citation
“…A previous study, ref. [45], showed that under Beaufort 7 wind conditions, when considering factors like ship length, water depth, and anchoring chain length, the radius is smaller than the radius derived from calculations involving the rule-based methods determined by Equation (8). Therefore, using the rule-based radius, as evident from the more conservative results presented in this paper, is considered a reasonable approach.…”
Section: Modeling Characteristic Regions Of the Port Of Ulsanmentioning
confidence: 71%
“…[7]. Additionally, sufficient data communication via satellite in the open ocean and network systems in coastal areas is important [8]. Furthermore, these ships have to be integrated with the technologies emerging in smart port systems, as ship operations are extensively linked with port data [9,10].…”
Section: Introduction 1research Backgroundmentioning
confidence: 99%